2008
DOI: 10.1590/s0103-90162008000600016
|View full text |Cite
|
Sign up to set email alerts
|

Microbial enzymatic activity and thermal effect in a tropical soil treated with organic materials

Abstract: Bacteria and fungi are the most active decomposers of organic materials in soil. They directly affect plant nutrient availability, and chemical and physical properties of soils. This investigation aimed at quantifying the effect of several organic materials on microbial activity of a Rhodic Eutrudox. Soil samples were incubated over a period of 91 days with the following organic materials: cattle manure (CM), earthworm humus (HM), and city sewage sludge from Barueri (BA) and Franca (FR). The activities of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…The production of extra cellular enzymes related to microbial biomass enhancement (Albiach et al, 2000). Cenciani et al (2008) also concluded that soil microbial carbon significant correlated to cellulose activities. This inferred that any change in soil enzymes activity would strongly influenced soil organic C pools.…”
Section: Relation Between Soil Loc Fractions and Microbial Characterimentioning
confidence: 96%
“…The production of extra cellular enzymes related to microbial biomass enhancement (Albiach et al, 2000). Cenciani et al (2008) also concluded that soil microbial carbon significant correlated to cellulose activities. This inferred that any change in soil enzymes activity would strongly influenced soil organic C pools.…”
Section: Relation Between Soil Loc Fractions and Microbial Characterimentioning
confidence: 96%
“…The overall cellulase activity in the soil samples containing earthworm casts was relatively low (261 μg glucose g -1 soil 24 h -1 ), when compared with other organic materials, but values were significantly higher than of the unamended control. These results are probably due to the relatively humified and stable composition that characterizes the earthworm humus (Cenciani et al, 2008). The sum of cellulase activity was lower in the sludge from Franca (273.4 μg glucose g -1 soil 24 h -1 ) than in sewage sludge from Barueri (367.7 μg glucose g -1 soil 24 h -1 ) (Table 2a), despite the high carbon contents in both sludges (Table 1).…”
Section: Cellulasementioning
confidence: 95%
“…It is possible that the pH influences these processes. In relatively acidic soil, as in FR sludge with pH 6.0, several ions are hydrolyzed and can react with organic compounds to form organic-complexes (Cenciani et al, 2008), differently from the Barueri sludge, with an alkaline pH of around 12 (Table 1).…”
Section: Cellulasementioning
confidence: 99%
See 2 more Smart Citations